2011
DOI: 10.1002/ird.685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Groundwater Level Depth and Irrigation Amount on Water Fluxes at the Groundwater Table and Water Use of Wheat

Abstract: Three irrigation water regimes (90.0, 67.5, and 45.0 mm) and five groundwater table depths (1.5, 2.0, 2.5, 3.0, and 3.5 m) were considered in a lysimeter experiment to investigate the effect of groundwater level and irrigation amount on water fluxes at the groundwater table and water use of wheat. Results show that deep percolation (irrigation of 16-23%) occurred to a considerable extent in the present irrigation level at a shallow groundwater table of 1.5-2.0 m. Capillary rise comprised 29% of the water use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 20 publications
6
21
0
Order By: Relevance
“…Using the Meyer equation (Wu et al, 1999), Ayars et al (2006) found that the maximum upward fluxes occur when the root zone is dry and groundwater table is shallow and the minimum upward fluxes occur when the root zone is wet, with either deep or shallow groundwater. Huo et al (2011) came to similar conclusions based on their lysimeter studies of the water use of wheat.…”
Section: Effects On the Water Usesupporting
confidence: 53%
See 2 more Smart Citations
“…Using the Meyer equation (Wu et al, 1999), Ayars et al (2006) found that the maximum upward fluxes occur when the root zone is dry and groundwater table is shallow and the minimum upward fluxes occur when the root zone is wet, with either deep or shallow groundwater. Huo et al (2011) came to similar conclusions based on their lysimeter studies of the water use of wheat.…”
Section: Effects On the Water Usesupporting
confidence: 53%
“…The quantification of upward fluxes from a shallow groundwater table is a significant topic that has been extensively researched (Ganiev, 1979;Zhang et al, 1999;Soppe and Ayars, 2003;Kahlown et al, 2005;Babajimopoulos et al, 2007;Yang et al, 2007;Huo et al, 2011). In the Fergana Valley, Ganiev (1979) studied over a period of four years the capillary rise from a shallow water table in lysimeter experiments under fallow and natural conditions, and cropped with cotton or alfalfa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of capillary rise as supplier of water to crops has been shown by many researchers (e.g. Huo et al, 2012;Talebnejad, and 90 Sepaskhah, 2015;Han et al, 2015); however we found only a few studies that use an integrated modelling approach (Xu et al, 2013;Zipper et al 2015) to quantify capillary rise for different hydrological conditions (including free drainage) using physically based approaches. In this study we explicitly consider the effect of crop type, soil type, weather year and drainage condition on capillary rise.…”
mentioning
confidence: 75%
“…al. [14] found that the wheat crop consumed 29% of its water demand from subsurface waters when the WTD is maintained at 1.5 m. They also observed that the contribution of subsurface irrigation helps in lowering down the WT. Ayars et.…”
Section: Sgw (Shallow Groundwater) Is An Important Resource Thatmentioning
confidence: 96%